Bioactivity of hydroxyapatite obtained from eggshell for potential use as bone cement - Gárcia-Sánchez, Karen; Quiñones, Iber J.; Gutierrez-M, Jose Oscar; Camargo-Amado, Ruben; Basante-Romo, Mónica J. (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Biomaterials have become a fundamental tool in tissue engineering and regenerative medicine because of their capacity to mimic the original tissue. Currently, bone cements are being studied as bone substitute biomaterials in different pathologies, also compounds with materials such as hydroxyapatite are analyzed to provide them bioactivity. In the present study, the main goal was to evaluate the bioactive nature of hydroxyapatite samples obtained from eggshells. Hydroxyapatite synthesis was performed by a wet chemical method, in which calcium oxide from eggshells and phosphoric acid were used as sources of calcium and phosphorus, respectively. The chemical characterization carried out by Raman spectroscopy and EDS showed that it was possible to obtain hydroxyapatite from this residue with a Ca/P ratio of 2,187. For the bioactivity study, the powder samples were immersed in simulated body fluid for 14 and 28 days.  Before and after the treatment the samples were characterized to determine their Ca/P ratio and behavior over time by Raman spectroscopy, and SEM-EDS microscopy. The characterization techniques allowed us to know that hydroxyapatite synthesized from eggshells had bioactive properties.  It is stable material in contact with the simulated body fluid, which suggests it is a great candidate to be used as an addition to conventional bone cement.